1987
DOI: 10.1037/0278-7393.13.3.456
|View full text |Cite
|
Sign up to set email alerts
|

Specific visual transfer in word identification.

Abstract: Prior presentation of a word can serve to enhance its later perceptual identification. A series of three experiments was designed to determine if this effect of prior experience depends on preserving the visual details of a word between its prior presentation and test. A first experiment revealed evidence of specific visual transfer only for words that were tested in lowercase. Words tested in lowercase that had been previously presented in lowercase were more readily identified than were those that had been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
210
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(228 citation statements)
references
References 30 publications
18
210
0
Order By: Relevance
“…For example, Jacoby and Hayman (1987) found that prior presentation of a word improved later perceptual identification of that word when specific physical details were retained. The ease with which a stimulus is perceived is often called perceptual fluency and depends on the degree of physical overlap between representations stored at study and stimuli presented at test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Jacoby and Hayman (1987) found that prior presentation of a word improved later perceptual identification of that word when specific physical details were retained. The ease with which a stimulus is perceived is often called perceptual fluency and depends on the degree of physical overlap between representations stored at study and stimuli presented at test.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several years, Jacoby and his colleagues have argued that perception can rely on memory for prior episodes (Jacoby, 1983a(Jacoby, , 1983bJacoby & Brooks, 1984;Jacoby & Hayman, 1987;Johnston, Dark, & Jacoby, 1985; see also Schacter, 1990). For example, Jacoby and Hayman (1987) found that prior presentation of a word improved later perceptual identification of that word when specific physical details were retained.…”
Section: Discussionmentioning
confidence: 99%
“…To observe robust effects, researchers typically need to contrive conditions that deviate from natural language experience. For example, voice and font effects are enhanced when attention is focused on surface attributes during study (Goldinger, 1996;Meehan & Pilotti, 1996) or when particularly salient attributes are used (Jacoby & Hayman, 1987;Kolers, 1976). Surface-specific effects are also most evident when transfer-appropriate processing is applied in test sessions; episodic memory is strongly expressed when study operations are repeated at test (Blaxton, 1989;GraY & Ryan, 1990).…”
Section: Lexical Processes Beyond Perception ?mentioning
confidence: 99%
“…In many articles, Jacoby ( 1983aJacoby ( , 1983bJacoby & Brooks, 1984;Jacoby & Dallas, 1981;Jacoby & Hayman, 1987;Jacoby & Witherspoon, 1982) has suggested nonanalytic word perception by comparison to stored episodes rather than to abstract nodes (see Feustel, Shiffrin, & Salasoo, 1983;Kirsner, Dunn, & Standen, 1987;Salasoo, Shiffrin, & Feustel, 1985). Although episodic theories of word perception have been frequently suggested, little formal modeling has occurred (except Salasoo et al, 1985).…”
Section: The Episodic Lexicon?mentioning
confidence: 99%
“…(e.g. Jolicoeur 1985;Jacoby & Hayman 1987). Fourth, imagining a stimulus produces repetition priming similar to actually perceiving it, suggesting that perceptual representations underlie both (e.g.…”
Section: Simulations and Situated Conceptualizations As Sources Of Prmentioning
confidence: 99%